BREED SUSCEPTIBILITY OF DOMESTIC DOGS TO ECTOPARASITE OF CTENOCEPHALIDES (SIPHONAPTERA, PULICIDAE) GENUS - Horb, K. O. (Scientific Progress & Innovations, 2020)
Among domestic carnivorous animals certain diseases are registered, the causative agents of which can infect not only dogs and cats, but also other animals and humans. Fleas of Ctenocephalides genus are ecto-parasites of domestic dogs and cats, which are known and spread most of all. These external parasites can be spreaders of many infectious and invasion diseases. The studies were conducted at the laboratory of the Department of Parasitology and Veterinary-Sanitary Expert Examination of Poltava State Agrarian Acade-my and “VetExpert” veterinary service (in the town of Poltava). The aim of the research was to study the peculiarities of susceptibility of different dog breeds to causative agents of ctenocephalosis. According to the results of the conducted investigation, it has been established that prevalence of dog infection varied from 35.58 to 84.12 %, while intensity of infection varied from 14.57 to 27.54 specimens of fleas per animal. Non-pedigree dogs and mongrels turned out to be susceptible to Ctenocephalides spp. most of all; prevalence reached 81.45 and 84.12 %, respectively, and average intensity of invasion – 27.54 and 21.37 speci-mens/animal. Utility and hunting dog breeds were less susceptible: ЕІ made 51.66 and 41.41% at ІІ – 18.40 and 16.23 specimens/animal respectively. Ctenocephalosis was diagnosed less frequently in dogs of decora-tive breeds: ЕІ made 35.58% and ІІ – 14.57 specimens/animal. At the same time, dogs of such breeds, as German sheep dog, Middle Asian sheep dog, Caucasian sheep dog, alabai, boerboel, Siberian huski, kone-korso, kurtshaar, English bulldog, toy-terrier, poodle, and fox-terrier turned out to be infected with Ctenocephalides spp. most of all: prevalence varied from 57.73 to 83.19 %. Dogs of yag-terrier and French bulldog breeds were infected least of all; ЕІ made 10.61 and 13.92% respectively. It was found out that long-wool dog breeds were susceptible to ctenocephalose invasion most of all; in such cases EI and II reached 70.60% and 20.24 specimens/animal. At the same time, short-wool dogs were less infected with causative agents of ctenocephalosis – 35.65% and 13.00 specimens/animal. The obtained data concerning breed susceptibility of dogs to ctenocaphalosis causative agents will enable to plan and conduct preventive measures more effectively, taking into account the peculiarities of animal breeds.